Motives, expectations and preparedness for higher education: a study of Education Development Unit (EDU) students at UCT - Zulu, Zibuyile (College of Accounting, 2025)
This study aims to identify the motives, expectations, and preparedness of first-year accounting students on the Education Development Unit (EDU) programme at the University of Cape Town (UCT) in South Africa. Understanding these factors is crucial for enhancing the success and transition of black students into higher education, especially considering the historical inequalities of Apartheid. A quantitative approach was employed, utilising a questionnaire administered to first-year accounting students on the EDU program. Responses from 85 students were obtained. Descriptive statistics were used to analyse the data. The findings reveal diverse motives for entering higher education, including career aspirations and personal development. Students' expectations include gaining knowledge, developing skills, and achieving academic success, though levels of preparedness vary. While students anticipated intellectual growth, they did not expect to develop better social skills. The findings reveal that students' time commitments were not aligned with university expectations. No gender differences were observed between male and female students. Additionally, no significant differences were identified between Thuthuka (black students with funding and support from the South African Institute of Charted Accountants (SAICA)) and non-Thuthuka students, nor between students who took English as a first language and those who did not. A recommendation stemming from the study is that educators should incorporate initiatives to develop interpersonal skills alongside academic training. These findings have practical implications for curriculum design and student support services, particularly catering for black students in South Africa.